North America - Johnston, Keith, 1844-1879; W. & A.K. Johnston Limited
This map shows North and Central America and the surrounding areas. Each country is outlined in color and each U.S. state is delineated and labeled. Cities, bodies of water, and geographic features are marked (with relief shown by hachures). There is an inset on the left side of the map showing the "Continuation of Alaska Peninsula."